2007
DOI: 10.1677/erc-06-0077
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Janus kinase 2 (JAK)/signal transducer and activator of transcription (STAT) genes: putative association of the STAT gene region with familial breast cancer

Abstract: The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway mediates the signals of a wide range of cytokines, growth factors and hormones. Thus, aberrant activation of the JAK/STAT pathway may predispose to malignancy due to deregulation of proliferation, differentiation or apoptosis. In this study, we investigated whether genetic variation in the JAK2 gene and the STAT gene region (STAT3, STAT5A and STAT5B) is associated with breast cancer (BC) risk. We carried out a case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 30 publications
(34 reference statements)
0
37
1
4
Order By: Relevance
“…It is notable that this SNP has been recently reported to be associated with the risk of developing breast cancer. 19 We evaluated the impact of rs6503691 in more detail by taking other prognostic factors into account. On univariate analysis, the leukocyte count, percentage blasts, spleen size, Sokal score and rs6503691 genotype were all significantly associated with response (Table 1B).…”
Section: Resultsmentioning
confidence: 99%
“…It is notable that this SNP has been recently reported to be associated with the risk of developing breast cancer. 19 We evaluated the impact of rs6503691 in more detail by taking other prognostic factors into account. On univariate analysis, the leukocyte count, percentage blasts, spleen size, Sokal score and rs6503691 genotype were all significantly associated with response (Table 1B).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is only one article that has investigated STAT3 polymorphisms in relation to cancer risk (Vaclavicek et al, 2007). Vaclavicek et al (2007) reported that, although rs2293152 and rs7211777 in the STAT3 gene were not individually associated with familial breast cancer, the haplotypes characterized by rs7211777 and a neighboring SNP rs6503691 in the STAT5B gene were found to modify the risk of familial breast cancer. In the present study, we showed for the first time that SNPs in the STAT3 gene were associated with decreased NSCLC risk.…”
Section: Discussionmentioning
confidence: 99%
“…These SNPs were selected based on i) previously published associations with various diseases (Ito et al, 2007;Vaclavicek et al, 2007;Barrett et al, 2008), thus increasing the chance of selecting SNPs with functional consequences, and ii) minor allele frequency of ≥0.1 in the Chinese population, using HapMap and National Center for Biotechnology Information dbSNP public databases.…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two SNPs in the JAK2 gene have been associated with central adiposity (rs7849191) and blood lipid levels (rs3780378) (21). Lastly, STAT5B SNP rs6503691 has been associated with breast cancer (22) and cholesterol levels in children with idiopathic GHD before, during, and after GH replacement (23), and SOCS2 SNP rs11107116 has been associated with peak height velocity during puberty (24) and adult height (25).…”
Section: Introductionmentioning
confidence: 99%